The Politeness Strategies In Rejection And Praise The Case Of Caught In Providence Youtube Channel - Helmita Helmita; Fajri Ilham Ananda Fajri Ilham Ananda (Jurnal Ilmiah Langue and Parole, 2026)
This research aims to analyze the use of politeness strategies in rejection and praise on the youtube channel Caught In Providence. This research uses (Brown and Levinsons 1987). Politeness theory to identify and classify the strategies used by Judge Frank Caprio and the defendants during interactions in the courtroom. Data were collected using purposive sampling from 20 of the most popular videos with over 5 million views, which contained expressions of rejection and praise. The method used was qualitative descriptive analysis to examine linguistic features, social context, and actions that threaten or preserve face. Face-threatening activities (FTAs) and face-saving actions (FSAs) in conversations were analyzed. The results of the research indicate that positive politeness and negative politeness strategies are often used to maintain mutual respect and minimize potential conflicts. In cases of rejection, Judge Frank Caprio tends to use indirect language, softened language, and empathy to protect the negative face of the defendants. Meanwhile, in situations involving praise, positive politeness strategies, such as giving praise, humor, and expressions of solidarity, are more dominant. This research shows that interactions in the Caught In Providence courtroom combine legal authority with interpersonal harmony and reflect a high awareness of social relationships and public perspectives.